Is postural tremor size controlled by interstitial potassium concentration in muscle?. Issue 7 (16th June 2004) - Lakie, M D; Hayes, N R; Combes, N; Langford, N
Abstract : Objectives: To determine whether factors associated with postural tremor operate by altering muscle interstitial K + . Methods: An experimental approach was used to investigate the effects of procedures designed to increase or decrease interstitial K + . Postural physiological tremor was measured by conventional means. Brief periods of ischaemic muscle activity were used to increase muscle interstitial K + . Infusion of the β2 agonist terbutaline was used to decrease plasma (and interstitial) K + . Blood samples were taken for the determination of plasma K + . Results: Ischaemia rapidly reduced tremor size, but only when the muscle was active. The β2 agonist produced a slow and progressive rise in tremor size that was almost exactly mirrored by a slow and progressive decrease in plasma K + . Conclusions: Ischaemic reduction of postural tremor has been attributed to effects on muscle spindles or an unexplained effect on muscle. This study showed that ischaemia did not reduce tremor size unless there was accompanying muscular activity. An accumulation of K + in the interstitium of the ischaemic active muscle may blunt the response of the muscle and reduce its fusion frequency, so that the force output becomes less pulsatile and tremor size decreases. When a β2 agonist is infused, the rise in tremor mirrors the resultant decrease in plasma K + . Decreased plasma K + reduces interstitial K + concentration and may produce greater muscular force fluctuation (more tremor). Many other factors that affect postural tremor size may exert their effect by altering plasma K + concentration, thereby changing the concentration of K + in the interstitial fluid.